Early Biomarker-Guided Prediction of Bloodstream Infection in Critically Ill Patients: C-Reactive Protein, Procalcitonin, and Leukocytes. (14th September 2022) - Hertz, Frederik Boetius; Ahlström, Magnus G; Bestle, Morten H; Hein, Lars; Mohr, Thomas; Lundgren, Jens D; Galle, Tina; Andersen, Mads Holmen; Murray, Daniel; Lindhardt, Anne; Itenov, Theis Skovsgaard; Jensen, Jens Ulrik Staehr
Abstract: Background: Bloodstream infections (BSIs) often lead to critical illness and death. The primary aim of this study was to determine the diagnostic accuracy of the biomarkers C-reactive protein (CRP), procalcitonin (PCT), and leukocyte count for the diagnosis of BSI in critically ill patients. Methods: This was a nested case–control study based on the Procalcitonin And Survival Study (PASS) trial (n = 1200). Patients who were admitted to the intensive care unit (ICU) <24 hours, and not expected to die within <24 hours, were recruited. For the current study, we included patients with a BSI within ±3 days of ICU admission and matched controls without a BSI in a 1:2 ratio. Diagnostic accuracy for BSI for the biomarkers on days 1, 2, and 3 of ICU admission was assessed. Sensitivity, specificity, and negative and positive predictive values were calculated for prespecified thresholds and for a data-driven cutoff. Results: In total, there were 525 patients (n = 175 cases, 350 controls). The fixed low threshold for all 3 biomarkers (CRP = 20 mg/L; leucocytes = 10 × 10 9 /L; PCT = 0.4 ng/mL) resulted in negative predictive values on day 1: CRP = 0.91; 95% CI, 0.75–1.00; leukocyte = 0.75; 95% CI, 0.68–0.81; PCT = 0.91; 95% CI, 0.84–0.96). Combining the 3 biomarkers yielded similar results as PCT alone ( P = .5). Conclusions: CRP and PCT could in most cases rule out BSI in critically ill patients. As almost no patients had low CRP and ∼20% had low PCT, a low PCT could be used, along with other information, to guide clinical decisions.